Mano po - Soriano, Maricel; Gomez, Richard; Aguion, Kris; Lamangan, Joel (Regal Home Video, 2002)
A compelling tale of a Chinese-Filipino family's search for identity and place in Philippine History. Told in the context of their struggles amid harsh contempory realities and the ties that bind them to a land that has been good to them despite the life-threatening circumtances that have now begun to hover over their lives.